How does social media influence expectations, decision making and experiences of childbirth? - Lawrence, Victoria; Richardson, Sonia; Philp, Lauren (British Journal of Midwifery, 2023)
Background/Aims: Ideological perceptions of normal, physiological birth can be potentially dangerous. Clinicians highlighted to the Health and Social Care Committee how social media affects this, believing that the 'pressure' of social media contributing to 'a big expectation of normality' among expectant parents. This review's aims were to explore the available literature to support this statement and provide a contemporary insight that incorporates the consequences of the COVID-19 pandemic. Methods: This review was a qualitative meta-synthesis of literature identified in April 2022 using seven subject specific electronic databases: CINAHL Plus, MEDLINE, AMED, APA PsychInfo, APA PyschArt, MIDIRS and The British Nursing Database. Five qualitative primary research papers were critiqued and summarised. Results: The first theme was focused on how social media reshapes and marginalises narratives of birth; the dominant narrative of medicalised birth is reinforced, but the curated narrative around physiological birth can also be problematic. The second theme encompassed how social media alters women's autonomy and agency in decision making about birth by affecting information sharing and their sense of connection. Conclusions: Social media can contribute to an ideological perception of normal birth, creating additional pressures on women. However, a medicalised portrayal of birth, which women conform to, dominates these spaces. Social media both supports, and threatens, women's ability to make informed decisions about childbirth.